Theology : the basics - McGrath, Alister E. (Wiley Blackwell, 2018)
This fourth edition of the international bestseller is the ideal introduction for those who are new to Christian theology. In this revised and expanded edition, the author introduces readers to the central ideas and beliefs, the key debates and the leading thinkers of Christianity. Throughout, the aim is to bring clarity and brevity to the central ideas of theology, both traditional and contemporary.